Effect of TDZ and 2, 4-D on peanut somatic embryogenesis and in vitro bud development - Joshi, Madhumita; Sujatha, K.; Hazra, Sulekha (Plant Cell Tissue and Organ Culture, 2008)
Failure of peanut somatic embryos to convert into plantlets is attributed to the abnormal development of the plumule. Thidiazuron (TDZ) was effective in the conversion of peanut somatic embryos to plantlets by triggering morphogenetic activity in the abnormal plumules of the rooted somatic embryos. The present study aimed to induce normal embryo differentiation by culturing the embryogenic masses in embryo development medium containing 2,4-D and various concentrations of TDZ. Although this was not achieved due to restricted somatic embryo development in the presence of TDZ, bud-like projections appeared in the embryogenic masses when these were cultured in media containing combinations of 2,4-D and TDZ. These projections developed into buds, which subsequently formed shoots and plantlets. The response varied with the concentration and exposure of TDZ. At lower concentrations, the buds appeared in a defined row in the equatorial region of the explant, and with extended incubation, more and more buds appeared in rows alongside the initial row. Induction of multiple buds in a defined row in this specific site (equatorial region) suggested the presence of potent cells around this region. At higher concentrations, these projections appeared in large numbers spread over the whole upper part of the embryogenic mass starting from the equatorial region. The ability of embryogenic mass to convert into organogenic mass and to produce large number of organogenic buds provides an excellent system for basic studies and for the genetic transformation of peanut.
Keywords: Arachis hypogaea; embyogenic mass; somatic embryogenesis; thidiazuron